Performance Evaluation of Schools Division in Mindanao: Education for All 2015 - Binag, Gee Marie S.; Eguia, Rec (JPAIR Multidisciplinary Research, 2012)
The study was conducted to evaluate the technical and productivity performance of school divisions in Mindanao from the period of 2002- 2010. The mean profile of input and output variables was computed using Mean the Technical and Allocative Efficiency scores and Total Factor Productivity were calculated using DEA with output orientation while the sources of inefficiency of the schools divisions were calculated using the Tobit Regression and the significance of the difference were calculated using SPSS version 16. Based on the findings among 48 school divisions in Mindanao 10 of these have achieved full technical efficiency level. Meanwhile, 38 schools division were least efficient due to lack of factors inputs like number of male and female enrollees, desk, classrooms and MOOE. A component of the productivity change is due more technological and total factor productivity changes with efficiency changes providing a gap. At 5 percent level of significance, there were significant differences in the technical efficiency and allocative efficiency scores of the school division when grouped according to regions where they belong. Thus, the study revealed that number of the desk and teachers were the Sources of inefficiencies of the school divisions.